Blast-Casting Mechanism and Parameter Optimization of a Benched Deep-Hole in an Opencast Coal Mine - Li Ma; Xingping Lai; Jianguo Zhang; Shuangshuang Xiao; Leiming Zhang; Yuhang Tu (Shock and Vibration)
During the research on bench deep-hole blast casting, the blast-casting parameters are directly related to the blast-casting results, so it could reveal the mechanism for improving the effect thereof. Based on the principle of the plane charge method, both the stress wave and detonation gas were considered to affect rock fragmentation and casting, a model of overburden fragmentation and casting process around the blasting hole was established, and bench deep-hole blast-casting behaviours were elucidated. By using the Factor Analysis Method (FAM), a correlation analysis model of factors influencing blast-casting results was built. The results proved that powder factor (or specific charge) ranked first in terms of its influence, followed by hole spacing, minimum resistance line, burden, and bench height. The formulae for calculating the limit powder factor value and the spacing of blasting holes were derived for different rock properties. The results showed that the optimum hole spacing was no more than 12.49 m and the powder factor was no more than 0.75 kg/m3, and it proved that an effective casting percentage (ECP) of 34% could be realized.